Neuromuscular responses and physiological patterns during a soccer simulation protocol. Artificial turf versus natural grass - Lopez-Fernandez, J.; Garcia-Unanue, J.; Sanchez-Sanchez, J.; Leon, M.; Hernando, E.; Gallardo, L. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Latest studies suggest similar performance of soccer players either on artificial turf (AT) or natural grass (NG). However, it is not clear if their muscular and physiological responses are also similar on both surfaces. This research aims to assess the influence of game surface on physiological patterns and neuromuscular responses of soccer players during a soccer simulation protocol (SSP) that incorporates repeated sprints and nonlinear actions at maximum speed. METHODS: Sixteen amateur soccer players completed three bouts of the SSP on both AT and NG. The mechanical behaviour of both surfaces was recorded and the order was randomly established for each player. The physiological responses were measured during the SSP. A contra-movement jump and a tensiomyography analysis of the rectus femoris (RF) and biceps femoris (BF) were assessed right before and right after the SSP. RESULTS: Both surfaces presented different mechanical properties. No differences among either surfaces or bouts were found for heart rate (HR) peak and HR mean (P>0.05). While the half-relaxation time of the RF on NG decreased after the SSP (right-leg: -44.430 ms; P=0.049; left-leg: -52.131 ms; P=0.008), the sustain time of the BF decreased after the SSP on AT (right-leg: +64.868 ms; P=0.007; left-leg: +87.564 ms; P<0.001). No differences between surfaces were found for the contra-movement jump. CONCLUSIONS: The mechanical behaviour of both surfaces does not differ enough to cause different physiological and neuromuscular responses. Playing on AT should cause similar neuromuscular responses to NG.